PERANAN SELAT MAKASSAR DAN KONTINUITAS HUBUNGAN KALIMANTAN BAGIAN TIMUR DAN SULAWESI BAGIAN BARAT - Andi Nuralang (Naditira Widya, 2009)
Archaeological and historical data discovered in the eastern part of Kalimantan and western Sulawesi indicates strong relationship between both regions, which dates back to the prehistoric period and flourished until today. Archaeological remains indicated Sulawesi to have more dominant influnces to that of Kalimantan. This article discusses the influnces of Sulawesi to cultural society at the Kalimantan region, also cultural continuity based on archaeological remains from both region.